469 The Role of Social Determinants of Health in Child Mortality and Survival Following Abusive Head Trauma. (1st April 2022) - Singer, Timothy; Warner, Claire; Mehl, Steven; Cain, Cary; Kralik, Stephen F.; Orman, Gunes; Desai, Nilesh; Sarpong, Kwabena; Donaruma, Marcella; Huisman, Thierry; Naik-Mathuria, Bindi; Weiner, Howard L.; et al.
Abstract : INTRODUCTION: Abusive Head Trauma (AHT) is a leading cause of preventable pediatric death in the United States, with mortality rates as high as 30. Although population-based studies implicate the Social Determinants of Health (SDOH), "the conditions in the environments where people are born, live, learn, work, play, worship, and age, " as risk factors for AHT mortality, patient-level series have not been widely reported. Examining patient-level SDOH data could provide valuable information for targeted interventions to prevent AHT mortality. METHODS: We included children <5 years with expert-confirmed AHT at our freestanding children's hospital from 3/2018-2/2021. Demographic, social, and clinical data were excerpted. Pediatric neuroradiologists reviewed imaging. Descriptive and inferential analyses were conducted with RStudio. RESULTS: Of 103 patients with AHT, 19 (18.4%) died and 84 (82.6%) survived. The cohorts were demographically similar. Housing status was not significantly different. Prior interactions with a social worker (11% vs 19%), Child Protective Services (42% vs. 32%), and law enforcement (44% vs. 32%) were frequently observed but not significantly different. Health access measures including insurance status and established care with a pediatrician were similar. Deceased children were more likely to have mothers who were jobless 64% vs. 40%, p = 0.042). Mothers of deceased children were younger (22 vs. 25 years, p = 0.038). Clinically, a strong association was observed between in-hospital mortality and injury severity on presentation (Glasgow Coma Scale, Injury Severity Score, Abbreviated Injury Scale), intubation, presence of hypoxic-ischemic injury, and percent of hospitalization in the intensive care unit. Frequency of neurosurgical intervention was equal between cohorts (32% vs. 23%, p = 0.39). CONCLUSION: Adverse SDOH were observed frequently in both cohorts, often at levels far exceeding state and national averages. Children who died from AHT were more likely to have younger, unemployed mothers.